Synthesis and functional properties of ZnO/CuO nanocomposite for gas sensing applications. Issue 1 (1st January 2022) - Bharathi, P.; Karthigeyan, S.; Krishna Mohan, M.
Abstract: ZnO/ CuO nanocomposite is one of the promising materials for gas sensing application. The p-n heterojunction formation plays vital role by providing more gas interaction sites with the analyte gas molecules. Formation of hetero junction improves the charge transport and reduces the operating temperature. Herein we report the simple synthesis and characterization of ZnO nanoparticles and ZnO/CuO nanocomposite using facile hydrothermal synthesis method. The preparedsamples confirm the hexagonal crystal structure. The morphological micrograph confirms the uniform growth of CuO nanoparticles on the ZnO matrix.